Assessment of quality of life and selected aspects of physical, psychological, social, and environmental functioning in patients treated for breast cancer 5 years after breast-conserving surgery or mastectomy - Magdalena Tarkowska; Iwona Głowacka-Mrotek; Tomasz Nowikiewicz; Agata Gastecka; Justyna Szymańska; Wojciech Hagner; Wojciech Zegarski (Kazimierz Wielki University, 2019)
Introduction: Breast cancer is the most common cancer in women in well-developed countries. Modern treatment for breast cancer is multimodal, with surgery being the mainstay of treatment. The aim of the study was to assess quality of life, self-efficacy, and satisfaction with life in patients treated for breast cancer with two different surgery types. Materials and methods: This study involved 360 women - 120 after mastectomy (MAS), 120 after breast-conserving surgery (BCT), and 120 healthy controls (CG). The standardized WHOQOL-BREF (abbreviated form) questionnaire, General Self-Efficacy Scale (GSES), and Satisfaction with Life Scale (SWLS) were used for measuring quality of life Results: As regards physical, psychological, social, and environmental functioning (WHOQOL-BREF), women after mastectomy had the worst scores (p